Primary-tertiary diamine-catalyzed Michael addition of ketones to isatylidenemalononitrile derivatives - Kumar, Akshay; Chimni, Swapandeep Singh (Beilstein Journal of Organic Chemistry, 2014)
Simple primary-tertiary diamines easily derived from natural primary amino acids were used to catalyze the Michael addition of ketones with isatylidenemalononitrile derivatives. Diamine 1a in combination with D-CSA as an additive provided Michael adducts in high yield (up to 94%) and excellent enantioselectivity (up to 99%). The catalyst 1a was successfully used to catalyze the three-component version of the reaction by a domino Knoevenagel–Michael sequence. The Michael adduct 4a was transformed into spirooxindole 6 by a reduction with sodium borohydride in a highly enantioselective manner.
Keywords: 3,3'-disubstituted oxindoles; Michael reaction; organocatalysis; primary-tertiary diamine; spirooxindoles